ACCOUNTING AT 'EREHWON' - Bexell, J. A. (The Accounting Review, 1927)
Abstract Professional speaker Dean Marshall made a notable contribution to business literature in the "Journal of Political Economy" for June, 1926, entitled "The Collegiate School of Business at Erehwon." In a somewhat allegorical form Dean Marshall traces the development of collegiate business education in the United States during the last ten years. He is correct in his statement that nowhere is found exactly such courses as he proposes. But the general trend of collegiate commercial education has followed his plan. His conclusions are evolutionary rather than revolutionary. The evolution of business education is stated in the following words: "The organization of material is now being modified, not because it was a failure, it was a distinct success, but because conditions seem to justify taking the next step. For one thing, in the last decade there has been a great increase in the amount of factual economic material available for use in the high schools and there will certainly be a still greater increase in the future. This seems to justify looking forward to a somewhat more mature and generalized presentation of our economic organization at the junior college level. For another thing, the materials of Instruction which Erehwon has developed in the various subdivisions of this field can now rather readily be arranged so as to give in a single course a more organic presentation of economic organization than was possible in the half-dozen somewhat specialized courses."